Immediate Dental Implant Placement in the Oncologic Setting: A Conceptual Framework. Issue 9 (September 2021) - Anolik, Rachel A.; Nelson, Jonas A.; Rosen, Evan B.; Disa, Joseph; Matros, Evan; Allen, Robert J.
Abstract : Summary: Historically, immediate dental implants have been reserved for patients with benign disease, with full dental rehabilitation rarely being accomplished in the oncologic setting due to concerns related to implant survival, flap compromise, and delay in initiation of adjuvant therapy. Recent developments in technology have made immediate dental implants using virtual surgical planning safe and reliable. At Memorial Sloan Kettering Cancer Center, we have implemented a workflow for immediate dental implant placement in the oncologic patient population that has become a routine part of maxillary and mandibular reconstruction. This approach begins with a multidisciplinary virtual surgical planning session and custom dental splints to be used for cutting and inset guides. Dental implants are placed intraoperatively at the time of tumor resection and reconstruction with the fibula flap. A temporary prosthesis, which can be worn during radiation therapy, is placed following a vestibuloplasty, approximately 4–6 weeks after the initial reconstruction. After the completion of radiation therapy and the resolution of edema, a permanent prosthesis is placed. When critically evaluating our experience, we have found that patients undergoing immediate dental implant placement have higher rates of implant survival and no delay in adjuvant therapy. The protocol described here in detail has successfully expanded the indications for immediate dental rehabilitation in the oncologic patient population.